Exceptionally high organic nitrogen concentrations in a semi-arid South Texas estuary susceptible to brown tide blooms. (15th March 2017) - Wetz, Michael S.; Cira, Emily K.; Sterba-Boatwright, Blair; Montagna, Paul A.; Palmer, Terence A.; Hayes, Kenneth C.
Abstract: Studies of estuarine eutrophication have tended to focus on systems with continually flowing rivers, while little is known about estuaries from semi-arid/arid regions. Here we report results from an assessment of water quality conditions in Baffin Bay, Texas, a shallow (<2–3 m) subtropical estuary located in a semi-arid region that has agriculture as the dominant (44%) watershed land use. Chlorophyll a averaged 28–30 μg/l in Baffin Bay from 2003 to 2013 and total Kjeldahl nitrogen (TKN) concentrations were also very high (116–120 μM), with concentrations of both variables exceeding those of most other Texas estuaries by 2–5 fold. More recent field sampling (2013–2015) showed that dissolved organic nitrogen concentrations in Baffin Bay (62 ± 14 μM) were >2 fold higher than in three other Texas estuaries. In contrast, inorganic nitrogen (ammonium, nitrate) and phosphate concentrations were relatively low. Statistically significant long-term annual increases in chlorophyll a and salinity were observed in Baffin Bay, while long-term seasonal increases were observed for water temperature and TKN. Overall, Baffin Bay is displaying multiple symptoms of eutrophication, namely very high organic carbon, organic nitrogen and chlorophyll concentrations, as well as symptoms not quantified here such as fish kills and episodic hypoxia. Much of the increase in chlorophyll in Baffin Bay, at least since ∼1990, have coincided with blooms of the mixotrophic phytoplankton species, Aureoumbra lagunensis, which is thought to be favored under high proportions of organic to inorganic nitrogen. Thus the high and possibly increasing organic nitrogen concentrations, coupled with a long-term annual increase in salinity and a long-term seasonal increase in water temperature are likely to promote additional brown tide blooms in this system in the future. Highlights: Baffin Bay (Texas) is displaying multiple symptoms of eutrophication. Organic nitrogen concentrations are 2–3 fold higher than other Texas estuaries. Long-term chlorophyll increase coincides with blooms of Aureoumbra lagunensis. Increasing organic nitrogen, salinity and water temperature favor A. lagunensis.